Postoperative vasoactive inotropic score is predictive of outcomes in pediatric heart transplantation. Issue 8 (3rd June 2020) - Tadros, Hanna J.; Lopez‐Colon, Dalia; Bleiweis, Mark S.; Fricker, Fredrick J.; Pietra, Biagio A.; Gupta, Dipankar
Abstract: Vasoactive inotrope score (VIS) is scarcely studied in pediatric orthotopic heart transplantation (pOHT). We conducted a retrospective review of pOHT (<21 years) recipients. Max VIS and mean VIS were calculated at 0‐24 and 24‐48 hours post‐pOHT. Patients were divided into groups based on ISHLT guidelines: high (>10) and low (≤10). In our group (n = 104), patients with high max and mean VIS groups at 0‐24 and 24‐48 hours had longer bypass times (high: >130 minutes; low: <108 minutes; P  < .05) and high max and mean VIS groups at 0‐24 hours had longer ischemic times (high: >215 minutes; low: <192 minutes; P  < .05). Patients with high max and mean VIS at 0‐24 and 24‐48 hours had longer hospital stay, ventilation, inotrope duration, more cardiac events, and acute kidney injury postoperatively ( P  < .05). High max VIS at 24‐48 hours and high mean VIS at 24‐48 hours had higher 3‐year mortality ( P  = .04; P  = .02). Multivariate analysis confirmed the association of VIS with short‐term outcomes. However, VIS was not identified as an independent predictor of mortality. The ROC curve exhibits 10 as the ideal cutoff with area under the curve >0.8 for primary graft dysfunction (PGD).